Long-Read Sequencing Annotation of the Transcriptome in DNA-PK Inactivated Cells - Song, Liwei; Yu, Mengjun; Jin, Renjing; Gu, Meng; Wang, Ziyu; Hou, Dailun; Xu, Shaofa; Wang, Jinghui; Ma, Teng (Frontiers in Oncology, 2022)
The DNA-dependent protein kinase catalytic subunit (DNA-PKcs) with a Ku70/Ku80 heterodimer constitutes the intact DNA-PK kinase, which is an upstream component of the DNA repair machinery that signals the DNA damage, orchestrates the DNA repair, and serves to maintain genome integrity. Beyond its role in DNA damage repair, the DNA-PK kinase is also implicated in transcriptional regulation and RNA metabolism, with an illuminated impact on tumor progression and therapeutic responses. However, the efforts to identify DNA-PK regulated transcriptomes are limited by short-read sequencing to resolve the full complexity of the transcriptome. Therefore, we leveraged the PacBio Single Molecule, Real-Time (SMRT) Sequencing platform to study the transcriptome after DNA-PK inactivation to further underscore the importance of its role in diseases. Our analysis revealed additional novel transcriptome and complex gene structures in the DNA-PK inactivated cells, identifying 8,355 high-confidence new isoforms from 3,197 annotated genes and 523 novel genes. Among them, 380 lncRNAs were identified. We validated these findings using computational approaches and confirmatory transcript quantification with short-read sequencing. Several novel isoforms representing distinct splicing events have been validated through PCR experiments. Our analyses provide novel insights into DNA-PK function in transcriptome regulation and RNA metabolism.